INNOVATIONS IN THE ACTIVITIES OF THE PRIMARY PHYSICAL CULTURE TEAM OF GENERAL EDUCATION SCHOOL (Scientific journal of the Fergana State University, 2025)
Innovations in the activities of the primary physical culture team of a general education school are a set of new approaches and methods aimed at meeting the demands of the times, enhancing students’ physical development, promoting a healthy lifestyle, and fostering team spirit. In this annotation, we will analyze the innovations being implemented in the activities of the primary school physical culture team.